The impact of knowledge management and innovation capacity on business results at FDI enterprises in Vietnam - Nhung, Nguyen Van; Thang, Vuong Quoc; Hoang, Tran Minh (Edelweiss Applied Science and Technology, 2024)
This research investigates the influence of knowledge management and innovation capacity on the business results of FDI enterprises in Vietnam. We applied Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Structural Equation Modeling (SEM) along with SPSS and AMOS for analyzing the dataset. Through statistical analysis and empirical data, the study demonstrates a positive correlation between effective knowledge management practices and enhanced innovation capacity, which collectively improve overall business results. The research results contribute to affirming the role of knowledge management and innovation in enabling businesses to achieve sustainable development goals.